The Impact of Board Size and Audit Committee Characteristics on Financial Performance in Foreign Exchange Banks: Evidence from Indonesia - Bahari, Samsul (Jurnal Penelitian IPTEKS, 2024)
The concept of corporate governance has played an important role, especially in the process of submitting financial reports. However, the literature reveals inconsistent findings regarding the impact of corporate governance characteristics on financial performance. Despite numerous studies on corporate governance, there remains a lack of evidence, particularly in the banking industry, specifically concerning foreign exchange banks in Indonesia. This study aims to investigate the influence of board size and audit committee characteristics, namely audit committee size, frequency of audit committee meetings, and audit committee expertise, as integral components of corporate governance, on financial performance. The type of this research is descriptive qualitative research that utilized data obtained from the annual reports published by the Financial Services Authority (OJK) and the websites of 38 foreign exchange banks in Indonesia from 2007 to 2021. The research findings indicate that board size exhibits a non-significant negative relationship with financial performance measured by Return on Assets (ROA) and Return on Equity (ROE). In addition, the results regarding audit committee size and frequency of meetings show no significant relationship with ROA and ROE proxied financial performance. However, audit committee expertise shows a significant negative relationship with financial performance as measured by ROE, and not significant with ROA. These findings will assist management in making informed decisions regarding optimizing board size and audit committee characteristics to meet the needs and interests of all stakeholders within the company. Overall, this research emphasizes the need for continuous improvement in corporate governance practices for sustainable growth and development.